The Bibles of the far right - Strømmen, Hannah M. (Oxford University Press, 2024)
"This study examines the role that Bibles have come to play in the worldview of the contemporary far right. It argues that references to biblical texts and "the Bible" are part of calls to defend Europe against Islam. Taking the case of far-right terrorism in Norway on 22 July 2011 as a starting point, the study maps continuities and connections between Bible-use in far-right terrorist manifestos, in the thought-leaders that inspire far-right violence, in conservative thinkers of Europe, and in historical forms of Bible-use that are being activated today. By drawing on Gilles Deleuze and Félix Guattari, this study proposes a way of doing biblical reception that maps how Bibles operate in the world as assemblages. Ultimately, The Bibles of the Far Right proposes new ways to understand political Bible-use today in order to respond to violence inspired by biblical texts"--